Zapisz w prostrzej postaci:
a. (x+4)+(2x-6)=
b.-(2y+3x)+(-4y+2x+1)=
c.-(x-2xy)-(4x+xy)+(xy-x)=
d.(x[do potegi 2]+2x+1)-(x[do potegi 2]-4x+3)=

Podane wyrażenia zapisz w najprostrzej postaci:
a. a-[a-(1-a)]=
b. -x-[-(1-x)-(x-1)]=
c. x-[y-(x-y)-x-(y-x)]=
d. 1-a-[1-(a-1)-2a-(1-3a)]-a-1=

20 pkt.!;))

3

Odpowiedzi

  • illa
  • Początkujący
2009-11-24T20:50:45+01:00
A.x+4+2x-6= 3x-2
b.-2y-3x-4y+2x+1=-6y-x+1
c.-x+2xy-4x-xy+xy-x=-6x+2xy
d.x(do pot.2)+2x+1-x(do pot.2)+4x-3=5x-2

a.a-[a-1+a]=a-a+1-a=-a+1
b.-x-[1+x-x+1]=-x-1-x+x-1=-x-2
c. x-[y-x+y-x-y+x]=x-y+x-y+x+y-x=2x-y
d.1-a-[1-a+1-2a-1+3a]-a-1=1-a-1+a-1+2a+1-3a-a-1=-1-2a

Powinn być dobrze ;)
  • Użytkownik Zadane
2009-11-24T20:52:31+01:00
A) (x+4)+(2x-6)=x+4+2x-6=3x-2
b.-(2y+3x)+(-4y+2x+1)=-2y-3x+-4y+2x+1=-6y-x+1
c.-(x-2xy)-(4x+xy)+(xy-x)=-x+2xy-4x-xy+xy-x=-6x+2xy
d.(x²+2x+1)-(x²-4x+3)=x²+2x+1-x²+4x-3=6x-2



a. a-[a-(1-a)]= a-[a-1+a]= a-a+1-a=-3a+1
b. -x-[-(1-x)-(x-1)]= -x-[-1+x-x+1]=-x+1+x-x+1=-x+2
c. x-[y-(x-y)-x-(y-x)]=x-[y-x+y-x-y+x]=x-y+x-y+x+y-x=2x-y
d. 1-a-[1-(a-1)-2a-(1-3a)]-a-1=1-a-[1-a+1-2a-1+3a]-a-1=1-a-1+a+1+2a+1-3a-a-1=a-1+a+1+2a+1-3a-a-1=-a
2009-11-24T21:04:04+01:00
A. (x+4)+(2x-6)=3x-2
b.-(2y+3x)+(-4y+2x+1)=-2y-3x-4y+2x+1=-2y-x+1
c.-(x-2xy)-(4x+xy)+(xy-x)=-x+2xy-4x-xy+xy-x=-6x+2xy
d.(x[do potegi 2]+2x+1)-(x[do potegi 2]-4x+3)=x²+2x+1-x²+4x-3=6x-2

Podane wyrażenia zapisz w najprostrzej postaci:
a. a-[a-(1-a)]=a-(2a-1)=-a-1
b. -x-[-(1-x)-(x-1)]=-x-(-1+x-x+1)=x-2
c. x-[y-(x-y)-x-(y-x)]=x-(x-2y)-2x-y=-2x+y
d. 1-a-[1-(a-1)-2a-(1-3a)]-a-1=1-a-(2-a-2a-1-5a)=-7a